2011
DOI: 10.2165/11593600-000000000-00000
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Hypertension and Sociodemographic Factors within the Scheduled Caste Community of the District Nadia, West Bengal, India

Abstract: The results of this investigation clearly indicate that there was a significant (p<0.001) role of dietary salt in the development of hypertension.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
11
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 14 publications
0
11
0
Order By: Relevance
“…10,15,16 These wide regional and urban-rural (33 vs 25%) variations 9 could be explained by the use of different definitions, non-uniform sensitivity and specificity of the measuring instruments, methodological nuances, sociocultural diversities 7 and food habits like traditional use of extra salt. [17][18][19] Although previously observed prevalence of hypertension among backward communities in West Bengal was bit lower (19.28%), 20 observed values from the current study might be considered as a relatively generalizable estimate for such poorresource settings by virtue of the representative population-based sampling.…”
Section: Discussionmentioning
confidence: 70%
See 3 more Smart Citations
“…10,15,16 These wide regional and urban-rural (33 vs 25%) variations 9 could be explained by the use of different definitions, non-uniform sensitivity and specificity of the measuring instruments, methodological nuances, sociocultural diversities 7 and food habits like traditional use of extra salt. [17][18][19] Although previously observed prevalence of hypertension among backward communities in West Bengal was bit lower (19.28%), 20 observed values from the current study might be considered as a relatively generalizable estimate for such poorresource settings by virtue of the representative population-based sampling.…”
Section: Discussionmentioning
confidence: 70%
“…20,21,24,[28][29][30][31] With reference to general caste, subjects belonging to backward caste were less likely to suffer from hypertension but among them, cases were more likely to remain undiagnosed, as also was observed previously in another nearby district. 20 Consistent with previous studies, 13,22,24,26 it was additionally found that participants with higher education were more likely to be hypertensive probably due to sedentary lifestyle and less likely to remain undiagnosed compared with their illiterate counterparts. Belonging to backward castes and having less education probably had negative influences on awareness and care-seeking resulting in delayed diagnosis or non-identification of cases.…”
Section: Discussionmentioning
confidence: 72%
See 2 more Smart Citations
“…Previous surveys in KSA reported a 5.3% prevalence of IDH more than two decades ago (4). Studies in different countries reported a prevalence of IDH ranging from 2-8%, mostly associated with males, younger adults, and obese individuals (19)(20)(21)(22)(23)(24). In this study, we will assess the current prevalence of IDH, characteristics, treatment modalities, patient' practices, risk factors and significant predictors which were not previously addressed to the best of our knowledge.…”
mentioning
confidence: 99%